Compact and cGMP-compliant automated synthesis of [18F]FSPG on the Trasis AllinOne™ - Rizwan Farooq; Thibault Gendron; Richard S. Edwards; Timothy H. Witney (EJNMMI Radiopharmacy and Chemistry)
Abstract Background (S)-4-(3-18F-Fluoropropyl)-ʟ-glutamic acid ([18F]FSPG) is a positron emission tomography radiotracer used to image system xc −, an antiporter that is upregulated in several cancers. Not only does imaging system xc − with [18F]FSPG identify tumours, but it can also provide an early readout of response and resistance to therapy. Unfortunately, the clinical production of [18F]FSPG has been hampered by a lack of robust, cGMP-compliant methods. Here, we report the automated synthesis of [18F]FSPG on the Trasis AllinOne™, overcoming previous limitations to provide a user-friendly method ready for clinical adoption. Results The optimised method provided [18F]FSPG in 33.5 ± 4.9% radiochemical yield in just 35 min when starting with 18–25 GBq. Importantly, this method could be scaled up to > 100 GBq starting activity with only a modest reduction in radiochemical yield, providing [18F]FSPG with a molar activity of 372 ± 65 GBq/µmol and excellent radiochemical purity (96.8 ± 1.1%). The formulated product was stable when produced with these high starting activities. Conclusions We have developed the first automated synthesis of [18F]FSPG on the Trasis AllinOne™. The method produces [18F]FSPG with excellent radiochemical purity and in high amounts suitable for large clinical trials and off-site distribution. The method expands the number of synthesis modules capable of producing [18F]FSPG and has been carefully designed for cGMP compliance to simplify regulatory approval for clinical production. The methods developed for the purification of high-activity [18F]FSPG are transferrable and should aid the development of clinical [18F]FSPG productions on other synthesis modules.